O atual papel da culpa na responsabilidade civil extracontratual - Audi, Ana Carolina Botto (2008)
The purpose of this paper is to verify the role of culpability in civil liability and to verify in what hypotheses it would be present in order to determine the compensation of damages, with a conclusion as to whether the Civil Code is subjective or objective. Initially, the general concepts of about fault liability and culpability are exposed, mentioning the development of civil liability over time and the reasons that led to reconsideration of the attachment to culpability. The peculiarities of the current system are also checked, since its main principle is human dignity, which results in the alteration of the cause of civil liability from culpability to unjust damage and the consequent socialization of the risk represented by the insurance agreement, concluding that today there are two general civil liability clauses within the legal system. Subsequently, absolute liability and the so-called indemnity charged for damages resulting from risk activities present in some specific laws are discussed. Finally, the sole paragraph of article 944 of the Civil Code is approached and considerations are made for its inclusion in the provision that upholds the quantification of the indemnity to then make considerations about the co-existence of fault liability and absolute liability within the Civil Code. The whole study was made in the light of human dignity and the need to compensate unjust damage for which it used the constitutional principles according to which all legal doctrines must be analyzed in view of the constitution of an equalitarian and fraternal society